Characteristics and treatment pathways in pediatric and adult hidradenitis suppurativa: An examination using real world dataCapsule Summary - Jill Hardin, PhD; Rupa Makadia, PhD; Shawn Black, PhD; Irene Lara-Corrales, MD; Lucia Z. Diaz, MD; Joslyn S. Kirby, MD; Cynthia M.C. DeKlotz, MD (Elsevier, 2023)
Background: Hidradenitis suppurativa (HS) is a chronic, debilitating, inflammatory disease. Contemporaneous real-world data can be used to elucidate the clinical treatment of pediatric patients and how treatment strategies compare with adult hidradenitis suppurativa patients. Objective: The objective of this study is to evaluate clinical and treatment characteristics of pediatric and adult HS patients. Methods: HS adult and pediatric patients were identified in 3 the United States administrative claims databases during the study period between 2016 to 2021. Patients were required to have 2 diagnostic codes for HS and have at least 365 days of prior observation time to the first HS diagnosis. Results: Pediatric and adult HS treatments were similar. The proportions of subjects treated with topical and oral antibiotic or oral antibiotic alone or topical medication alone or surgery alone covered 90% of the treated pediatric subjects and 91% of treated adult subjects. The remaining proportion of subjects received other treatment combinations. Limitations: The databases represent subjects with commercial or government insurance coverage and thus do not necessarily represent the broader US population. The databases do not capture information about medications obtained without insurance. Conclusions: Although subtle differences exist, this study confirms that topical and systemic therapeutic treatment of HS in adults and adolescents is very similar.